(untitled) (Nigerian Journal of Technology, 2016)
The purpose of this research was to develop models for the prediction of responses from orthogonal metal cutting process that are responsible for the machinability ratings of this technological system. Mild steel work-piece material that is representative sample for various industrial applications was machined. The various industrial applications of this representative sample range from mechanical shafts to fasteners, screws and hydraulic jack. These machine elements require high degree of surface finish. A fifteen-run based Box-Behnken response surface design was created using widely established machining parameters, namely cutting speed, feed rate and depth of cut. The optimum predicted responses from the orthogonal cutting process for the optimal process parameters are 0.1742 micron, 0.4933 micron, 0.1845 micron, 0.3673 micron, 794.6839 seconds and 19.642 seconds for the Ra, Rz, Rq, Rt, TL and M/C time respectively. The associated desirabilities for these optimum responses are 1.000000, 1.000000, 1.000000, 1.000000, 0.524122, and 0.361858 respectively. http://dx.doi.org/10.4314/njt.v36i1.13